Pengawasan Pemerintahan Daerah Kabupaten Lingga Terhadap Izin Pertambangan Bauksit Tahun 2011 - ARDI PUTRA; Isri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Indonesia is one of the largest archipelagic country in the world that is so large and has spread almost all over the country. One of these resources is the result of mining. Lingga regency is one area that is located in the province of Riau Islands which have the potential mining of natural resources is considerable potential as a source of local revenue and state. one of these is mining bauxite mining.This study aims to determine the District level Government oversight phallus against Bauxite mining license in 2011 and to determine the constraints on Government Oversight Lingga District to permit the mining of bauxite in 2011. use of resources through informen. in this study, the informen is Lingga District Council Member, Department of Mines and Energy Lingga District, District Environment Agency Lingga, Mining Company, communities around the mine. while the data collection techniques consisted of interviews, documentation and observation with the source data consists of primary data and secondary data.Of the results showed that the District Government Oversight Lingga against Bauxite Mining License in 2011 with pegawasan mechanism has not been running at max. constraints on Government Oversight Lingga District to permit bauxite mining in 2011 is internal constraints and external constraints.Keyword: Mining, Oversight and Local Government